ONE FOR ALL , 4 FROM 1 ! – AN INNOVATION IN MAKING DENTULOUS IMPRESSIONS WITH ADJUSTABLE TRAYS - Kamya Mahajan; Niharika Reddy; Monalisha Das; G. Ajay Kumar (International Journal of Medical Science And Diagnosis Research, 2020)
Aim: It aims to provide an easy and efficient method of recording dentulous impressions by adjusting a single tray for various mouth sizes. Settings and Design/Methods and Material: Sectioning the maxillary and mandibular tray each in three parts and attaching 3 screws (regular stainless-steel wood screws were used) in the upper and 2 screws in the lower tray was done A demonstration model for the same has been constructed with nickel-titanium screws. The objective of writing the article is to propose the idea and demonstrate the functioning of the tray. Results: The trays were sectioned, screwing and unscrewing was done (with-Taparia flat tip mini head screw driver - 10.0 x 1.2 mm) and change in tray size from number 1 to 4 and vice-versa was observed. Matrix bands were placed on the sides to provide stability to the tray and to prevent movement of the sectioned parts while in use. Conclusion: The expandable tray is an easy and effective method of recording impressions. It can be easily modified according to the clinical scenario saving on valuable clinical time and effort. Keywords: expandable tray, dentulous tray, impression making, modified perforated tray, adjustable tray